EFFECTS OF ERYTHROPOIETIN PRETREATMENT ON LIVER, KIDNEY, HEART TISSUE IN PENTYLENTETRAZOL-INDUCED SEIZURES; EVALUATION IN TERMS OF OXIDATIVE MARKERS, PROLIDASE AND SIALIC ACID - Ayşegül Kapucu; Zülal Kaptan; Kadriye Akgün Dar; İslim Kaleler; Gülay Üzüm (İstanbul Tıp Fakültesi Dergisi)
Objective: The effects of erythropoietin (EPO) which has been frequently studied as an anti-epileptic agent, on peripheral tissues have not been investigated. This study investigated the effects on malondialdehyde (MDA), advanced protein oxidation products (AOPP), superoxide dismutase (SOD), prolidase and sialic acid (SA) levels in the heart, kidney and liver tissues of EPO pretreatment in pentylenetetrazole (PTZ)-induced seizures. Materials and Method: Thirty three male adult rats were divided into three groups. A saline-injected control group, a 60 mg/kg PTZ-injected group to induce seizures and a 3000 IU/kg EPO-injected group 24 hours before seizures. After seizure severity and seizure latency were scored, the rats sacrificed, the tissues were immediately removed for biochemical analyses. Results: The PTZ-induced seizures increased MDA in kidney (p<0.01) and AOPP in liver (p<0.05) but didn’t alter these markers in heart tissue. In all three tissues, SOD didn’t change due to seizures. The SA levels increased in the heart (p<0.001), de creased in the kidney (p<0.001), and were unchanged in liver. Prolidase increased (p<0.05) only in kidney, and was unchanged in other tissues. EPO-pretreatment decreased seizure severity and increased seizure latency. It prevented the increase in MDA in the kidney (p<0.01) but increased AOPP (p<0.05) anddecreased SOD (p<0.01) and further increased prolidase more than the seizures increased (p<0.01). EPO-pretreatment prevented the increase in AOPP in the liver (p<0.05) but was ineffective in PTZ-induced SA changes in the heart and kidney. Conclusion: We think that the increase in the heart SA level in seizures is an original finding and deserves investigation in the context of seizure-related cardiac arrhytmias. Also, despite the EPO’s anti-seizure effect, increased protein oxidaiton and prolidase, especially in the kidney, is an other important finding that needs further research.